2013
DOI: 10.1073/pnas.1317192110
|View full text |Cite
|
Sign up to set email alerts
|

Convergence in feeding posture occurs through different genetic loci in independently evolved cave populations of Astyanax mexicanus

Abstract: When an organism colonizes a new environment, it needs to adapt both morphologically and behaviorally to survive and thrive. Although recent progress has been made in understanding the genetic architecture underlying morphological evolution, behavioral evolution is poorly understood. Here, we use the Mexican cavefish, Astyanax mexicanus, to study the genetic basis for convergent evolution of feeding posture. When river-dwelling surface fish became entrapped in the caves, they were confronted with dramatic chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(133 citation statements)
references
References 26 publications
4
125
4
Order By: Relevance
“…Because cavefish show enhanced tastebud numbers mostly at the epidermis of the lower jaw facing the bottom of the pool, it was once suggested that these gustatory structures were linked to bottom-feeding posture (Schemmel, 1980), as cavefish feed at the bottom with their anteroposterior body axis oriented at a ~45° angle to the substrate. In contrast, when surface fish feed at the bottom, they orient their anteroposterior body axis perpendicular to the bottom and cannot stabilize their body posture in darkness; however, a series of genetic analyses using F 2 hybrids showed no correlation between bottom-feeding posture and these gustatory traits, as well as other cranial morphologies, suggesting that this bottom-feeding posture is instead based upon changes to the central nervous system (Kowalko et al, 2013b). Furthermore, QTL mapping revealed that the QTL for this bottom-feeding posture is not associated with the shh locus, revealing that these traits evolved without shh mutation; conversely, tastebud number is controlled by an shh overexpression (Figure 13.3).…”
Section: Enhancement In the Tastebud Systemmentioning
confidence: 93%
See 2 more Smart Citations
“…Because cavefish show enhanced tastebud numbers mostly at the epidermis of the lower jaw facing the bottom of the pool, it was once suggested that these gustatory structures were linked to bottom-feeding posture (Schemmel, 1980), as cavefish feed at the bottom with their anteroposterior body axis oriented at a ~45° angle to the substrate. In contrast, when surface fish feed at the bottom, they orient their anteroposterior body axis perpendicular to the bottom and cannot stabilize their body posture in darkness; however, a series of genetic analyses using F 2 hybrids showed no correlation between bottom-feeding posture and these gustatory traits, as well as other cranial morphologies, suggesting that this bottom-feeding posture is instead based upon changes to the central nervous system (Kowalko et al, 2013b). Furthermore, QTL mapping revealed that the QTL for this bottom-feeding posture is not associated with the shh locus, revealing that these traits evolved without shh mutation; conversely, tastebud number is controlled by an shh overexpression (Figure 13.3).…”
Section: Enhancement In the Tastebud Systemmentioning
confidence: 93%
“…The molecular pathways leading to VAB and (Yoshizawa et al, 2012;Kowalko et al, 2013b) Eye size Amino acid sensing Taste bud number (Protas et al, 2008) Eye size VAB EO SN number Feeding angle FIGURE 13.3 See legend next page associated changes in SN number and eye size may be distinct (Yoshizawa et al, 2012), but the correlations among these traits suggest that the reduction of eye size provides more space for SN at the eye orbit and therefore promotes VAB. Alternatively, multi-trait QTL clustering (i.e., where genes that regulate each different trait form a cluster in a confined area within the genome) may link suites of traits that are necessary for adaptation.…”
Section: Genetic Basis For the Evolution Of Vab And Its Sensory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have argued that evolution is fundamentally stochastic and unpredictable [3], while others have proposed that constraints commonly limit available phenotypic options, leading to parallelism and predictability [4]. Although parallel genotypic adaptation has been demonstrated across a diverse range of taxa at the intraspecific level [5][6][7][8][9][10][11], the widespread occurrence of parallel evolution across a clade has only rarely been shown [12,13]. The potential role of environmental change in driving parallel evolution also remains poorly understood [14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Astyanax cave morphs have lost their eyes and their pigmentation, and they have also lost sleep 12,13 , schooling 14,15 and hierarchical aggressive behaviour [16][17][18] . On the other hand, they have gained adaptive behaviours such as attraction to vibrations 19 , increased exploratory [20][21][22][23][24] and food searching behaviour 17 , and a special feeding posture 25,26 . This is sometimes referred to as 'the cavefish behavioural syndrome'.…”
mentioning
confidence: 99%